2017
DOI: 10.2967/jnumed.116.180984
|View full text |Cite
|
Sign up to set email alerts
|

Localization of Unknown Primary Site with 68Ga-DOTATOC PET/CT in Patients with Metastatic Neuroendocrine Tumor

Abstract: Localization of the site of the unknown primary tumor is critical for surgical treatment of patients presenting with neuroendocrine tumor (NET) with metastases. Methods: Forty patients with metastatic NET and unknown primary site underwent 68 Ga-DOTATOC PET/ CT in a single-site prospective study. The 68 Ga-DOTATOC PET/ CT was considered true-positive if the positive primary site was confirmed by histology or follow-up imaging. The scan was considered false-positive if no primary lesion was found corresponding … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
24
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
5
4

Relationship

2
7

Authors

Journals

citations
Cited by 35 publications
(25 citation statements)
references
References 20 publications
1
24
0
Order By: Relevance
“…A more recent study conducted by Menda, and colleagues studied the value of 68 Ga-DOTATOC PET/CT scan in 40 patients with metastatic NET but no identified primary site. They reported that 68 Ga-DOTATOC PET/ CT identified primary site in 38% of the cases [17]. These results agree with our data, where 68 Ga-DOTATOC PET/ CT identified the primary NET site in 45% of our cases with unknown primary.…”
Section: Discussionsupporting
confidence: 92%
“…A more recent study conducted by Menda, and colleagues studied the value of 68 Ga-DOTATOC PET/CT scan in 40 patients with metastatic NET but no identified primary site. They reported that 68 Ga-DOTATOC PET/ CT identified primary site in 38% of the cases [17]. These results agree with our data, where 68 Ga-DOTATOC PET/ CT identified the primary NET site in 45% of our cases with unknown primary.…”
Section: Discussionsupporting
confidence: 92%
“…Although CT exposes patients to negative effects of ionising radiation, it is easy, fast, relatively cheap, and recommended by most oncological guidelines for determining the stage of disease. The diagnostic examination tools that are also used to determine the primary focus are magnetic resonance imaging (MRI) and scintigraphic tests, such as somatostatin receptor scintigraphy (SRS) [ 8 ]. However, MRI is expensive and not easily available in some facilities.…”
Section: Discussionmentioning
confidence: 99%
“…Neuroendocrine tumours can also be imaged with nuclear medicine techniques that utilise two types of radiolabelling, namely, receptor expression and metabolic activity of the tumour [ 13 ]. In 2017, a study showed that 68 Ga-DOTA-TOC PET/CT using the 68 Ga-DOTA-D-Phe 1 -Try 3 -Octreotide label was helpful in localising primary neuroendocrine tumours in 37% of patients with disseminated neoplastic disease in whom conventional imaging techniques, such as CT or MRI, could not contribute to final diagnosis [ 8 ]. This examination is particularly useful in patients with an unknown primary focus in low-grade and intermediate-grade metastases.…”
Section: Discussionmentioning
confidence: 99%
“…There were 4 eligible papers (Table 3) that reported on performance of 68 Ga-DOTATOC PET/CT for detecting an unknown primary in patients with extensive metastatic disease (15,18,22,23). The overall success rate was 40 of 91 or 43.9%.…”
Section: Unknown Primary (Summary Statistics)mentioning
confidence: 99%